Decreased local immune response and retained HPV gene expression during chemoradiotherapy are associated with treatment resistance and death from cervical cancer. Issue 7 (4th December 2019) - Cosper, Pippa F.; McNair, Christopher; González, Iván; Wong, Nathan; Knudsen, Karen E.; Chen, Jason J.; Markovina, Stephanie; Schwarz, Julie K.; Grigsby, Perry W.; Wang, Xiaowei
Abstract : More than one‐third of patients with locally advanced cervical cancer do not respond to chemoradiation therapy (CRT). We aimed to characterize the transcriptional landscape of paired human cervical tumors before and during CRT in order to gain insight into the evolution of treatment response and to elucidate mechanisms of treatment resistance. We prospectively collected cervical tumor biopsies from 115 patients both before and 3 weeks into CRT. RNA‐sequencing, Gene Set Enrichment Analysis and HPV gene expression were performed on 20 paired samples that had adequate neoplastic tissue mid‐treatment. Tumors from patients with no evidence of disease (NED) at last follow‐up had enrichment in pathways related to the immune response both pretreatment and mid‐treatment, while tumors from patients dead of disease (DOD) demonstrated enrichment in biosynthetic and mitotic pathways but not in immune‐related pathways. Patients DOD had decreased expression of T‐cell and cytolytic genes and increased expression of PD‐L2 mid‐treatment compared to patients NED. Histological and immunohistochemical analysis revealed a decrease in tumor‐associated lymphocytes (TAL) during CRT in all patients but tumors from patients DOD had a significantly more pronounced decrease in TALs and CD8+ cells mid‐treatment, which was validated in a larger mid‐treatment cohort. Finally, patients DOD retained more HPV E6/E7 gene expression during CRT and this was associated with increased expression of genes driving mitosis, which was corroborated in vitro . Our results suggest that decreased local immune response and retained HPV gene expression may be acting together to promote treatment resistance during CRT in patients with cervical cancer. Abstract : What's new? Approximately 30% of cervical cancer patients are resistant to chemoradiation therapy but the causes of treatment resistance are unknown. Here the authors profiled gene expression of paired human cervical tumors before and during chemoradiation. Patients who were resistant to treatment and died of the disease showed a decreased local immune response and increased expression of biosynthetic and mitotic pathways. The results point to a combined role of diminished antitumor immunity and maintained expression of human papilloma virus E6/E7 oncogenes in patients failing chemoradiation treatment.